Employment Equity in Canada: The Legacy of the Abella Report - CAROL AGÃ“CS (University of Toronto Press, 2014)
The Abella Royal Commission was struck in June 1983 at a time when Canadian society and politics were embroiled in struggles surrounding social justice and inequality. The era of the 1970s through the mid- 1980s was marked by activism by advocates for women, racialized groups, persons with disabilities, and Aboriginal peoples who were organizing politically and raising demands that the inequality they experienced be addressed. In 1982 Canadaâ€™s Charter of Rights and Freedoms was adopted, infl uenced by a remarkable grass roots campaign by women across Canada to ensure that gender equality rights would be protected. The three major political parties adopted equity measures that resulted in an increase in the number of women elected to Parliament, and womenâ€™s voices began to matter in the politics of the time ( Harder 2006 , 68â€“70). By the mid-1980s there had been nearly two decades of experience with human rights processes marked by signifi cant decisions of courts, tribunals, and arbitrators, which set out workersâ€™ rights and clarifi ed employersâ€™ responsibilities for discriminatory acts in the workplace. Yet the human rights system placed the burden of change largely on individual survivors of discrimination, leaving in place the structures and systems that excluded and marginalized them. While human rights codes and the Charter of Rights permitted employers to undertake voluntary affi rmative action, very few did. Demands for a proactive and mandatory approach to addressing workplace inequality found a response from the Liberal government of Pierre Trudeau with the announcement of the Royal Commission on Equality in Employment and the appointment of Judge Abella, then of the Ontario Provincial Court, as sole commissioner. Her terms of reference were â€œto inquire into the most effi cient, effective and equitable means of promoting employment opportunities, eliminating systemic discrimination and assisting all individuals to compete for employment opportunities on an equal basisâ€ ( Abella 1984 , ii). Only sixteen months after the commission was announced, Judge Abella tabled her landmark report. It was supported by extensive public consultations across Canada and by a separate volume of thirty-four research reports by experts whose names are still identifi ed with path-breaking work on workplace equality.